Effect of the Family-Centered Empowerment Model on the Resilience of Parents of Children with Mental Retardation - saeideh mazidi; Mohammad-Ali jahani; seyed-Amir soltani; golbahar akhoundzadeh (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: A significant number of children with intellectual disability and mental retardation are added to the country's population annually causing a lot of psychological pressure on the family. The present study aimed to determine the effect of the family-centered empowerment model on the resilience of parents of children with mental retardation. Materials and Methods: This clinical trial study was conducted in 2021 in Aliabad-e katul, Iran, on the parents of mentally retarded children in two groups of test group and control group (24 people in each group) by conducting pre- and post-test through simple random sampling. Six sessions were held for the test group. In the control group, training and routine care were performed. The Connor and Davidson's Resilience Questionnaire was used as data collection tool. The collected data was analyzed in SPSS software (version 23). Results: In terms of the mean resilience score, a significant difference was observed between the test group before and after the intervention (P<0.001). Additionally, by removing the pre-test effect, a significant difference was seen between the test and control groups (P<0.001, Eta=0.48); therefore, 29% of the changes in the average score of parents' resilience were caused by the effect of the family-centered empowerment model. Conclusion: Considering the effectiveness of the family-centered empowerment model on parents' resilience and the importance of parents' role in caring for mentally retarded children, this low-cost and effective treatment method can be used in caring for and empowering parents.